2013
DOI: 10.1002/chin.201315199
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Furandiones from an Endophytic Aspergillus terreus Residing in Malus halliana

Abstract: isolation and structure elucidation of two new furandione derivatives, asperterone B (I) and C (II), which show moderate cytotoxic activities against the human colorectal carcinoma SW1116

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Due to the isolation of lesser amount we were not able to perform biological activities of these compounds, but the butenolides have gained special attention as α-glucosidase, cytotoxic and antiinflammatory agents. [28][29][30] Previous research has identified them as distinguishing characteristics of αglucosidase inhibitory actions. Recently butenolides showed the promising activity against the influenza viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the isolation of lesser amount we were not able to perform biological activities of these compounds, but the butenolides have gained special attention as α-glucosidase, cytotoxic and antiinflammatory agents. [28][29][30] Previous research has identified them as distinguishing characteristics of αglucosidase inhibitory actions. Recently butenolides showed the promising activity against the influenza viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Enantia chlorantha Oliv. Brine shrimp larvae cytotoxicity and bacterial activity [171] Expansol C (197) Penicillium expansum…”
Section: Tiliacora Triandramentioning
confidence: 99%
“…Compounds 37 and 38 showed significant cytotoxicity against PC3 (prostate cancer) cell line with IC 50 30.6 and 32.2 lM, respectively. Among the isolated compounds was trypacidin (40) which displayed activity against PC3 with IC 50 19.9 lM. Trypacidin also exhibited cytotoxicity against PC3D (multiple drug resistance cells), A549, and NCI-H460 with IC 50 39.6, 33.8, and 31 lM, respectively.…”
Section: Endophyte-host Interactionmentioning
confidence: 99%
“…Compounds 45 and 46 exhibited moderate cytotoxicity against human colorectal carcinoma SW1116 cells with IC 50 values of 57.5 and 71.0 lM, respectively. [40] N- (5,6,9,11a-Tetrahydro-1,2,3-trihydroxy-6-methyl-9-oxo-6aH-cyclohepta[a]naphthalen-6a-yl)acetamide (47) was isolated from an Aspergillus spp. endophyte from the seeds of Gloriosa superba and was found to possess activity comparable to the standard anticancer drugs mitomycin-C and 5-FU when tested against six cancer cell lines.…”
Section: Endophyte-host Interactionmentioning
confidence: 99%
See 1 more Smart Citation